2016
DOI: 10.4172/2161-0711.1000481
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Providers Knowledge, Attitude and Practices Related to Hepatitis C Screening and Treatment in the Oral Direct Acting Antiviral Agents Era

Abstract: BackgroundThere are over 3 million Americans infected with hepatitis C virus (HCV). Despite recent advances in HCV treatment, a major barrier to care remains a limited number of treaters. HCV therapy provision by primary care providers (PCPs) could expand access by increasing the pool of HCV treating clinicians.ObjectiveTo characterize current HCV care practices, willingness and self-efficacy of PCPs to become HCV treaters.Design, participants and main measuresTwo hundred and seventy one PCPs were identified f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…HCV treatment is often restricted by payers to patients with advanced fibrosis forcing PCPs to perform additional tests like a fibroscan that requires another complex level of understanding [24, 25]. Time restraints, knowledge gaps, easy access to the specialty referral, apprehension of medicolegal litigation, lack of HCV treatment in PCP quality measures, and provider restrictions on the prescription of independent HCV treatment are some of the reasons why PCPs are not comfortable treating hepatitis C [23, 26, 27]. Definitely, voluntary participation by PCPs is still the key factor here.…”
Section: Discussionmentioning
confidence: 99%
“…HCV treatment is often restricted by payers to patients with advanced fibrosis forcing PCPs to perform additional tests like a fibroscan that requires another complex level of understanding [24, 25]. Time restraints, knowledge gaps, easy access to the specialty referral, apprehension of medicolegal litigation, lack of HCV treatment in PCP quality measures, and provider restrictions on the prescription of independent HCV treatment are some of the reasons why PCPs are not comfortable treating hepatitis C [23, 26, 27]. Definitely, voluntary participation by PCPs is still the key factor here.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, primary care providers may lack knowledge about or confidence in providing hepatitis C treatment. 18 Multidisciplinary, team-based approaches for treating hepatitis C in primary care can address provider barriers and increase patient access and improve treatment outcomes. 19 Understanding the elements of effective hepatitis C treatment in primary care and dissemination of effective strategies could provide additional support to primary care practices considering provision of hepatitis C treatment in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Falade-Nwulia et al showed that a majority of primary care physicians (PCPs) (89%) referred HCV-infected patients to subspecialty clinics [ 11 ]. Market surveys in the US by Shiffman et al reported that 80% of HCV patients are managed by 20% of gastroenterologists [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Falade-Nwulia et al reported that the majority of PCPs (77%) were aware of the availability of new oral direct-acting agents, and more than two-thirds of them (67%) had correctly identified HCV genotype as an important part of the HCV treatment decision [ 11 ]. However, a significant proportion of residents were unaware of the available treatments for CHC in the setting of varies comorbidities.…”
Section: Discussionmentioning
confidence: 99%